The study was conducted to obtain the effect of using flash card during learning with jigsaw cooperative model on student` activity and their achievement - Aditya Prayoga; Darlen Sikumbang; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The study was conducted  to obtain the effect of using flash card during   learning with jigsaw cooperative model  on student` activity and their achievement. This study used  pretest-postest not equivalent designed on sample which was selected  using cluster random sampling sample technique. The data of student` concept mastery were obtained from  test (pretest and posttest), observation sheet (students learning activities) and student`s  respons questionnairet about this study. The student`s concept mastery was categorized according to Bloom Taxonomy namely  Data was analyzed using  t-test on the SPSS17 program.The  N-gain  score obtained showed that  the experimental class was better than  the control ones.  The study indicated that the flash card usage affecting student`s concept mastery espescially on comprehensiveness (C2) aspect, but not analysis skill (C4) aspect.  The average  student learning activity of experiment class was 75,12 %  which was high category. Based on the stud it can be concluded that the used of  flash card in Jigsaw  cooperative learning model  significantly enhanced  student`s  learning activities and their concept  mastery. Keywords: Flash card, Jigsaw, student learning activity, material mastery, matter material of Virus.